Draw the graphs of (i) y = x2 – x – 6 (ii) y = 6 – x – x2 and find zeros in each case. What do you notice?
Answers
Answered by
157
Dear Student,
graph of 1: (i) y = x2 – x – 6 is shown in green color in attachment image.
graph of 1: (i) y = 6 – x – x2 is shown in orange
color in attachment image.
zeros of both equations:
1) x2 – x – 6
![{x }^{2} - x - 6 = 0 \\ \\ {x}^{2} - 3x + 2x - 6 = 0 \\ \\ x(x - 3) + 2(x - 3) = 0 \\ \\ (x - 3)(x + 2) = 0 \\ x - = 0 \\ x = 3 \\ (x + 2) = 0 \\ x = - 2 {x }^{2} - x - 6 = 0 \\ \\ {x}^{2} - 3x + 2x - 6 = 0 \\ \\ x(x - 3) + 2(x - 3) = 0 \\ \\ (x - 3)(x + 2) = 0 \\ x - = 0 \\ x = 3 \\ (x + 2) = 0 \\ x = - 2](https://tex.z-dn.net/?f=+%7Bx+%7D%5E%7B2%7D++-+x+-+6+%3D+0+%5C%5C++%5C%5C++%7Bx%7D%5E%7B2%7D+-+3x+%2B+2x+-+6+%3D+0+%5C%5C++%5C%5C+x%28x+-+3%29+%2B+2%28x+-+3%29+%3D+0+%5C%5C++%5C%5C+%28x+-+3%29%28x+%2B+2%29+%3D+0+%5C%5C+x+-++%3D+0+%5C%5C+x+%3D+3+%5C%5C+%28x+%2B+2%29++%3D+0+%5C%5C+x+%3D++-+2)
2)
![6 - x - {x}^{2} = 0 \\ \\ - {x}^{2} - x + 6 = 0 \: \: \: \: or \\ {x}^{2} + x - 6 = 0 \\ \\ {x}^{2} + 3x - 2x - 6 = 0 \\ \\x (x + 3) - 2(x + 3) = 0 \\ \\ (x + 3)(x - 2) = 0 \\ \\ x + 3 = 0 \\ \\ x = - 3 \\ \\ x - 2 = 0 \\ \\ x = 2 6 - x - {x}^{2} = 0 \\ \\ - {x}^{2} - x + 6 = 0 \: \: \: \: or \\ {x}^{2} + x - 6 = 0 \\ \\ {x}^{2} + 3x - 2x - 6 = 0 \\ \\x (x + 3) - 2(x + 3) = 0 \\ \\ (x + 3)(x - 2) = 0 \\ \\ x + 3 = 0 \\ \\ x = - 3 \\ \\ x - 2 = 0 \\ \\ x = 2](https://tex.z-dn.net/?f=6+-+x+-++%7Bx%7D%5E%7B2%7D++%3D+0+%5C%5C++%5C%5C++-++%7Bx%7D%5E%7B2%7D++-+x+%2B+6+%3D+0+%5C%3A++%5C%3A++%5C%3A++%5C%3A+or+%5C%5C++%7Bx%7D%5E%7B2%7D++%2B+x+-+6+%3D+0+%5C%5C++%5C%5C++%7Bx%7D%5E%7B2%7D++%2B+3x+-+2x+-+6+%3D+0+%5C%5C++%5C%5Cx+%28x+%2B+3%29+-+2%28x+%2B+3%29+%3D+0+%5C%5C++%5C%5C+%28x+%2B+3%29%28x+-+2%29+%3D+0+%5C%5C++%5C%5C+x+%2B+3+%3D+0+%5C%5C++%5C%5C+x+%3D++-+3+%5C%5C++%5C%5C+x+-+2+%3D+0+%5C%5C++%5C%5C+x+%3D+2)
hope the solution helps you.
graph of 1: (i) y = x2 – x – 6 is shown in green color in attachment image.
graph of 1: (i) y = 6 – x – x2 is shown in orange
color in attachment image.
zeros of both equations:
1) x2 – x – 6
2)
hope the solution helps you.
Attachments:
![](https://hi-static.z-dn.net/files/d3c/926348863f981c02c5a4f230f3aa4cd2.jpg)
Answered by
25
Step-by-step explanation:
This is the answer for your questions
Attachments:
![](https://hi-static.z-dn.net/files/d99/37195fddf0e099d5a1ecdb9117d88dfe.jpg)
Similar questions